2022
DOI: 10.1021/acs.macromol.2c01305
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Degradable Polymers with Promising Mechanical Properties by Hydrogen Transfer Polymerization

Abstract: Hydrogen transfer polymerization (HTP) of vinyl monomers with active protons has resulted in heterochain polymers with attractive biodegradability and biocompatibility, which should enable it to be one of the most promising synthetic techniques. However, the molecular weight of the resultant polymers from HTP has been shown to be rather low, such that the products have nearly no practical application. The present work focuses on employing HTP to synthesize high-molecular-weight polymers and preparing biomateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Scheme 10 Strategy towards high molar mass oxa-Michael polymers; scheme adapted from ref. [70] In detail, they found that higher molar masses can be obtained in the polymerization of HEA when the temperature is kept at -5 °C for 12 h and increased to 80 °C for another 6 h with 1 mol% P2-t Bu as catalyst. By using low temperatures in the early polymerization stage, the Rauhut-Currier side reaction could be suppressed.…”
Section: Coupled Poly(ether-ester)smentioning
confidence: 99%
See 4 more Smart Citations
“…Scheme 10 Strategy towards high molar mass oxa-Michael polymers; scheme adapted from ref. [70] In detail, they found that higher molar masses can be obtained in the polymerization of HEA when the temperature is kept at -5 °C for 12 h and increased to 80 °C for another 6 h with 1 mol% P2-t Bu as catalyst. By using low temperatures in the early polymerization stage, the Rauhut-Currier side reaction could be suppressed.…”
Section: Coupled Poly(ether-ester)smentioning
confidence: 99%
“…over 24 h at 80 °C which is the highest that has ever been reported for polymers derived from oxa-Michael reactions. [70] The obtained polymer was further used to prepare biodegradable materials by UV-curing with microfluidic spinning. [70] Hyperbranched poly(ether-ester)s…”
Section: Coupled Poly(ether-ester)smentioning
confidence: 99%
See 3 more Smart Citations